Application for the diagnosis of pneumonia based on Pneumonia Severity Index (PSI) values - Elyza Wahyuni; Ahmad Ramadhan (IAES Indonesia Section, 2018)
There has been considerable research that addresses the diagnosis of pneumonia based on symptoms experienced by the patient, some using artificial intelligent methods such as monoton and non monoton methods with mixed results, based on previous studies to develop and improve previous research deficiencies because they refer to the results is expected to be useful by experts, especially lung specialists in Indonesia, The reference used by Indonesian pulmonary specialist is the value of Pneumonia Severity Index (PSI) which is used to classify Pneumonia level, then the expected results are qualitative and unambiguous outputs therefore fuzzy logic Sugeno method is very suitable to overcome the problem. Fuzzy logic Sugeno has been successfully applied in pneumonia disease and matched with the Pneumonia Severity Index Score in the amount of 75% based on 4 data has been tested.